2022
DOI: 10.1155/2022/6534626
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of Synuclein‐γ and Snai1 Contributes to Poor Clinical Prognosis in Oral Squamous Cell Carcinoma Patients

Abstract: Synuclein-γ (SNCG) and Snai1 play an important role in the occurrence and development of different types of malignant tumors. However, the association between SNCG and Snai1 and the effect of their combination on oral squamous cell carcinoma (OSCC) are unknown. The purpose of this study was to assess the expression of SNCG and Snai1 in OSCC tissues and their role in the genesis, development, diagnosis, and prognosis of OSCC. In this study, we first analyzed the Gene Expression Omnibus (GEO) database to determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 42 publications
(41 reference statements)
0
1
0
Order By: Relevance
“…We have previous reported that SNCG is highly expressed in the saliva, serum, and tissues of OSCC patients and proposed that SNCG could be a potential novel diagnostic marker for OSCC [20,21]. We have also shown that upregulation of SNCG contributes to poor prognosis in OSCC patients [13].…”
Section: Discussionmentioning
confidence: 92%
“…We have previous reported that SNCG is highly expressed in the saliva, serum, and tissues of OSCC patients and proposed that SNCG could be a potential novel diagnostic marker for OSCC [20,21]. We have also shown that upregulation of SNCG contributes to poor prognosis in OSCC patients [13].…”
Section: Discussionmentioning
confidence: 92%